Hypoxia regulates CD9-mediated keratinocyte migration via the P38/MAPK pathway - Jiang, Xupin (Nature Publishing Group, 2014)
Keratinocyte migration is an early event in the wound healing process. Although we previously found that CD9 downregulation is required for the keratinocyte migration during wound repair, the mechanism of how CD9 expression is regulated remains unclear. Here, we observed the effect of hypoxia (2% O(2)) on CD9 expression and keratinocyte migration. CD9 expression was downregulated and keratinocyte migration was increased under hypoxic conditions. In addition, CD9 overexpression reversed hypoxia-induced cell migration. We also found that hypoxia activated the p38/MAPK pathway. SB203580, a p38/MAPK inhibitor, increased CD9 expression and inhibited keratinocyte migration under hypoxia, while MKK6 (Glu) overexpression decreased CD9 expression and promoted hypoxic keratinocyte migration. Our results demonstrate that hypoxia regulates CD9 expression and CD9-mediated keratinocyte migration via the p38/MAPK pathway.